ANALISIS KAIDAH ‘URF PADA TRADISI MENDHEM ARI-ARI DALAM KEPERCAYAAN JAWA - Achmad Arif; Muhammad Akhlis Azamuddin Tifani; Nadia Sulistyawati; Teguh Eka Prasetya (Journal of Indonesian Comparative of Syari'ah Law, 2025)
Javanese people are known to hold on to the traditions of their ancestors. However, many young people just follow the tradition without knowing the beliefs contained and the law in Islam. The purpose of this study is to explain the Mendhem Ari-Ari Tradition in Javanese beliefs in Lidah Wetan Village according to the analysis of 'urf rules. This research is a qualitative research with descriptive-analytical research typology based on primary and secondary data collection methods as well as data collection methods through observation, interviews and documentation. The findings of this research: 1) The tradition of Mendhem Ari-Ari in Javanese beliefs in Lidah Wetan Village, Lakarsantri District, Surabaya City is carried out by using flower sesarat and wishing tools and then covering the grave with a basket for 40 days. 2) The review of the analysis of the rules of 'urf on this tradition is punished as a tradition that should not be done because it does not fulfil one of the requirements of urf and is categorised as fasid urf. But it can be done as long as it does not conflict with Islamic law.